2018
DOI: 10.36469/9785
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden of Contraception Management in Spain

Abstract: Background: A wide variety of contraceptive methods are available, some of them reimbursed by the Spanish National Health System (SNHS). However, the number of unintended pregnancies (UP) is still significant, leading to a high economic burden, mainly derived from non-adherence to and the incorrect use of contraceptive methods. Objectives: This study aims to estimate the economic burden associated with reversible contraception management in Spain, from the perspectives of both the SNHS and women, over a 5-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Despite its recommendation and of being a more economical option [26], the use of LARCs continues to be relatively low when compared to SARCs, a fact that has also been stated in studies conducted in other European countries such as Sweden, where 2 out of 10 women used LARCs [7]. It continues to be a more frequent contraception option in women aged over 30 years old [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its recommendation and of being a more economical option [26], the use of LARCs continues to be relatively low when compared to SARCs, a fact that has also been stated in studies conducted in other European countries such as Sweden, where 2 out of 10 women used LARCs [7]. It continues to be a more frequent contraception option in women aged over 30 years old [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, access to counselling on contraception and sexual education are not uniformly egalitarian throughout the country, as they depend on regional policies [19]. Thus, while they are practically fully funded in some regions, there are deficits in others [26].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a study conducted in Spain also showed that young women, aged up to 29 years, preferred to use SARC methods, such as combined oral contraceptive, vaginal ring, and male condom, for contraception. (15) This result highlights the importance of broader education and easier access to LARC methods to the population, especially young women, to prevent unintended pregnancies.…”
Section: ❚ Discussionmentioning
confidence: 97%